2022
DOI: 10.1155/2022/4042962
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Trends of Human Monkeypox Cases in Northern, Southern, Western, and Eastern Regions in Europe: A Cross-Sectional Study

Abstract: Background. The growing amount of monkeypox cases in non-endemic regions raises concerns in societies as a potential pandemic. This study highlights the prevalence and epidemiological trends of a human monkeypox outbreak in various regions in Europe. Methods. This cross-sectional study was conducted in the Department of Physiology, College of Medicine, King Saud University, Riyadh, Saudi Arabia. The data about the monkeypox outbreak in European countries were recorded by the World Health Organization (WHO), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 9 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…The study revealed the swift dissemination of human Mpox throughout the four subregions, affecting a total of 30 European states and impacting 6077 persons. The rise in Mpox cases was also seen, with incidences documented in Western Europe (2599 cases, accounting for 42.76% of the total), Southern Europe (1932 cases, representing 31.79% of the total), Northern Europe (1487 cases, comprising 24.46% of the total), and Eastern Europe (59 cases, making up 0.97% of the total 18 . Moreover, it has been reported that there has been an increasing incidence of Mpox cases in several European nations starting from May 2022 18 .…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…The study revealed the swift dissemination of human Mpox throughout the four subregions, affecting a total of 30 European states and impacting 6077 persons. The rise in Mpox cases was also seen, with incidences documented in Western Europe (2599 cases, accounting for 42.76% of the total), Southern Europe (1932 cases, representing 31.79% of the total), Northern Europe (1487 cases, comprising 24.46% of the total), and Eastern Europe (59 cases, making up 0.97% of the total 18 . Moreover, it has been reported that there has been an increasing incidence of Mpox cases in several European nations starting from May 2022 18 .…”
Section: Resultsmentioning
confidence: 92%
“…The rise in Mpox cases was also seen, with incidences documented in Western Europe (2599 cases, accounting for 42.76% of the total), Southern Europe (1932 cases, representing 31.79% of the total), Northern Europe (1487 cases, comprising 24.46% of the total), and Eastern Europe (59 cases, making up 0.97% of the total 18 . Moreover, it has been reported that there has been an increasing incidence of Mpox cases in several European nations starting from May 2022 18 . Significantly, Western European countries such as Switzerland (131), Germany (1304), Belgium (168), France (604), Austria (31), and the Netherlands (352) have reported notable instances of MPOX cases.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…A few months ago, the WHO expressed serious concern regarding the epidemiological situation in Europe, classifying it to be at high risk due to the spreading of the monkeypox in 30 European countries, where it infected more than 6000 subjects [ 100 ]. From January to October 2022, the global situations of monkeypox cases and deaths in non-endemic countries is well described in Table 2 [ 101 ].…”
Section: Discussionmentioning
confidence: 99%